Challenges to tackling antimicrobial resistance : economic and policy responses - Anderson, Michael; Cecchini, Michelle; Mossialos, Elias (Cambridge University Press, 2019)
Collected works that focus on the current changes in European health care systems and economic and health policies, with regards to antimicrobial resistance. Intended for professional public.
European Observatory on Health Systems and Policies
Keywords: pozorovací studie jako téma; antibakteriální látky; veřejné zdravotnictví; Health Policy; poskytování zdravotní péče; Delivery of Health Care; Anti-Bacterial Agents; Drug Resistance, Microbial; Evropa; zdravotní politika; farmacie a farmakologie; politologie, politika, zdravotní politika; Europe; antibiotická rezistence; Economics; Observational Studies as Topic; ekonomika